Clonal distribution of monophasic Salmonella enterica subsp. enterica serotype 4,[5],12:i:- in the Czech Republic - Myšková, Petra; Oslanecová, Lucia; Drahovská, Hana; Karpíšková, Renáta (Foodborne pathogens and disease, 2014)
Abstract Salmonella 4,[5],12:i:- has become the third most common serotype in Europe, including the Czech Republic. In this study, phenotypic and genotypic methods for a more detailed description of this serotype were used. Analysis of a limited number of isolates revealed that 76% of them belonged to phage type DT193. Also, rare phage types DT208 and U311 were identified. In total, 88.6% of the isolates were resistant to at least four antimicrobial agents. In this study, 24 multilocus variable-number tandem-repeat analysis profiles were detected, and some of them matched with the profiles recently described in Europe.
Keywords: Drug Resistance, Multiple, Bacterial; Salmonella enterica; séroskupina; mnohočetná bakteriální léková rezistence; Bacteriophage Typing; Česká republika; fagotypizace; potravinářská mikrobiologie; Czech Republic; kontaminace potravin; Animals; Food Microbiology; Flagellin; Food Contamination; flagelin; zvířata; Charadriiformes; Minisatellite Repeats; Serogroup; minisatelitní repetice